Kajian Kritis terhadap Pengaturan Pemilihan Gubernur Bupati dan Walikota di Indonesia Tahun 2020 - M Muslih (Universitas Batanghari Jambi, 2020)
The selection of regional heads in the perspective of the law is identical to the implementation of the law, as the state of law then every activity should be based on legal regulations as a guide as well as a legal benchmark is not tender an action related to the selection of On the other hand the legislation that regulates the selection of regional heads is relatively numerous and is spread over several statutory regulatory documents. The ideality of the regional head elections is strongly influenced by the level of public law awareness, where one indicator is the knowledge (identification) of the law. If the identification of the legal norm encountered a problem due to a pattern of less efficient legal communication will provide a burden of influence on the level of legal awareness of society which in turn will affect the quality of regional head selection. This article aims to describe how easy it is to know and understand the legal norms of regional head elections in Indonesia. The scope of this writing discredited the high dynamics and widespread the spread of the electoral regulations of the regional head, therefore the methodology used is normative legal research methods with qualitative analysis. One of the modern legal properties is its accurate predicting. Departing from the teaching, the setting of regional head elections in such a way will cause a domino effect/implication, difficult to identify positive norms, consequently legal knowledge and the understanding of law selection of the head of the Deaarah will be difficult to achieve. This reality causes a level of legal awareness that is expected to be difficult to realize, the awareness of the law is not ideal, will lead to the implementation of the head of the territory is not ideal. Such conditions will potentially encourage the election of regional head candidates who are also not ideal.